Reinterpretasi Paradigma Penelitian Kualitatif di Era Kecerdasan Buatan - Saleh, Muhammad; Yuliasti, Indra; Nadir, Sri Wahyuni (Jurnal Ilmu Sosial, Humaniora dan Seni, 2026)
This article aims to examine paradigms in qualitative research from a philosophical perspective and to explore their relevance in addressing the challenges and complexities of the modern world. Qualitative research is grounded in ontological, epistemological, methodological, and axiological frameworks that differ from those of quantitative approaches. Through a literature review, this article discusses five key paradigms that form the foundation of qualitative research: post-positivism, social constructivism, postmodernism, pragmatism, and critical theory. The novelty of this article lies in its reinterpretation of these paradigms within the context of technological developments, particularly artificial intelligence (AI), and their implications for the validity, ethics, and integrity of qualitative research. A descriptive-critical analysis is employed to evaluate how these paradigms remain relevant and can adapt to the needs of contemporary research. The study finds that qualitative paradigms are not only essential for understanding complex social realities, but also must be strengthened through philosophical reflection in response to the challenges of digitalization.